Rancang Bangun Aplikasi Peramalan Permintaan Produk dengan Metode Pemulusan Eksponensial Winter pada De Sam's Bakery &Donuts - Prasetyo, Dimas Bandung; Sulistiowati, Sulistiowati; Sudarmaningtyas, Pantjawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: De Sam's Bakery & Donuts is one of the companies engaged in the industrial production of bread which is located on the road Rungkut Madya 15. The problem that occurs is when the customer selects the desired type of cake, but the product is not enough. This can lead to customer disappointment to the company, even the company can be left by customers resulting company lost profits. This happens because so far in determining demand, the company has not used the method only based on estimates.Solutions offered to correct the problem is to use the company's forecasting method can predict product demand for a specific period. Forecasting used method Exponential Smoothing forecasting Winter, because based on autocorrelation analysis using Minitab 14, it is known that the data pattern of demand is seasonal and there is a tendency to trend.Based on trial results, this study resulted in product demand forecasting applications using Exponential Smoothing Methods Winter. Applications can predict product demand for the next three periods based on the data demand of the product in the previous period. Based on the test results obtained by the results of 83.4% so that the application of forecasting demand for products included in the category of very feasible to be used.Keywords: Applications, Forecasting, Demand, Exponential Smoothing Winter